Training on School and Madrasa Work Plans to Improve Education Quality Standards - Aries Fitriani; Arma Adha Afyfah; Zamzam Mustofa; Erwin Inu Dwi Saputra (Academia Open, 2025)
General Background: Education plays a pivotal role in shaping human resources and national development, requiring systematic planning and management to ensure quality improvement. Specific Background: In Ponorogo Regency, although more than 1,700 educational institutions exist, many schools and madrasahs have not fully utilized the School/Madrasah Work Plan (RKSM) as a strategic instrument, often perceiving it merely as administrative compliance. Knowledge Gap: This limited understanding and inconsistent implementation of RKSM hinder efforts to elevate educational quality standards, highlighting the need for capacity-building programs. Aims: This study aims to evaluate the effectiveness of training based on the Asset-Based Community Development (ABCD) approach in enhancing educators’ competence in preparing RKSM. Results: A pre-test and post-test comparison revealed a significant improvement, with mean scores increasing from 43.33 to 74.17, supported by t-test analysis showing high statistical significance (p < 0.005). Novelty: Unlike conventional approaches, the use of the ABCD framework emphasizes local assets—teachers, facilities, and community support—transforming planning into a participatory and contextually relevant process. Implications: The findings confirm that ABCD-based training strengthens educational planning, fosters collaboration among stakeholders, and contributes to sustainable quality enhancement in schools and madrasahs across Ponorogo. Highlights: Training with the ABCD approach significantly improved educators’ planning skills. Pre-test to post-test scores rose from 43.33 to 74.17 with strong significance. Asset-based methods foster collaboration and sustainable quality enhancement. Keywords: RKSM, Education Quality, ABCD Approach, Teacher Competence